2013
DOI: 10.1007/s10488-013-0491-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Consultation Calls for Clinic Supervisors in Supporting Large-Scale Dissemination of Evidence-Based Treatments for Children

Abstract: This study explores the content and process of consultation provided to clinic supervisors within the context of a statewide training program in an evidence-based practice. Minute-to-minute live coding of consultation calls with clinic supervisors was conducted in order to identify the content and distribution of call topics. Results indicated that approximately half of the total speaking time was spent on a range of clinically relevant topics (e.g., cognitive-behavioral therapy techniques, fidelity to the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…To date, EBTDC has provided training and a full year of distance-learning consultation to 1,552 clinicians and supervisors across 186 of the 346 clinics. The therapies supported by the EBTDC include CBT for depression, trauma-focused CBT, Coping Power, and Parent Management Training for DBDs (Gleacher et al, 2011; Nadeem et al, In press; Pimentel, Hoagwood, Albano, & Regan, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…To date, EBTDC has provided training and a full year of distance-learning consultation to 1,552 clinicians and supervisors across 186 of the 346 clinics. The therapies supported by the EBTDC include CBT for depression, trauma-focused CBT, Coping Power, and Parent Management Training for DBDs (Gleacher et al, 2011; Nadeem et al, In press; Pimentel, Hoagwood, Albano, & Regan, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…However, the limited empirical research on supervision is primarily descriptive or exploratory in nature (Hoge et al, 2011), despite findings from one study that suggest that supervision may account for 16% of the variance in client treatment outcomes—approximately double the amount commonly attributed to specific treatment interventions (8%; Callahan, Almstrom, Swift, Borja, & Heath, 2009). There also is increasing theoretical (Nadeem et al, 2013) and empirical work on a related, but distinct area, EBT-focused expert consultation (e.g., Bearman et al, 2013; Beidas, Edmunds, Marcus, & Kendall, 2012; Funderburk et al, 2015). While this is an important area of research, expert consultation is a costly resource (Herschell et al, 2010; Stewart et al, 2016), whereas providing clinical supervision of EBT through workplace-based supervision, utilizing existing supervisory staff, may provide a cost-effective, feasible alternative.…”
mentioning
confidence: 99%
“…Here, practitioners not only have access to interactive in‐person training workshops but also to ongoing support from clinical experts and from group members as they learn and apply EBTs in their particular work environment. In fact, some preliminary findings have suggested that ongoing clinical consultation appears to be a promising strategy for helping practitioners and organizations address some common challenges to implementation, and to improve learning of EBTs and the translation of training into practice (Fritz et al., ; Nadeem, Gleacher, & Beidas, ; Nadeem, Gleacher, Pimentel et al., ).…”
mentioning
confidence: 99%